2016
DOI: 10.7732/kjpr.2016.29.3.313
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of ‘Dongchul’ Persimmon (Diospyros kaki Thunb.) Fruit Grown in Gangwondo, Korea

Abstract: -Persimmon has long been established as one of the major fruits in Korea. The southern parts of Korea were traditionally the pocket areas for good persimmon production; however, rising temperatures have gradually rendered the southern regions unsuitable for successful harvest. Ecology of fruit growing areas affects the productivity of various types of crops, including fruit trees such as persimmon. The quality characteristics of the fruit of persimmon cv. Dongchul grown in Gangwondo, which lies in the northern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Sharma (2015) [24] revealed a value of 6.69 and 6.50 mg/100 g for total phenols in fully ripened Hachiya fruits with and without peel, respectively. On the other hand, Kim et al (2016) [31] revealed 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging capacity of 75.97, 70.12, 71.77, and 72.00 per cent in Dongchul, Daebong, Kyengsan Bans, and Sangju Doongsi, cultivar of persimmon, respectively. In Karaj 12 cultivar of persimmon, a value of 92.00 per cent was noticed for antioxidant activity by Naser et al (2018) [23] .…”
Section: Chemical Characteristicsmentioning
confidence: 99%
“…Sharma (2015) [24] revealed a value of 6.69 and 6.50 mg/100 g for total phenols in fully ripened Hachiya fruits with and without peel, respectively. On the other hand, Kim et al (2016) [31] revealed 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging capacity of 75.97, 70.12, 71.77, and 72.00 per cent in Dongchul, Daebong, Kyengsan Bans, and Sangju Doongsi, cultivar of persimmon, respectively. In Karaj 12 cultivar of persimmon, a value of 92.00 per cent was noticed for antioxidant activity by Naser et al (2018) [23] .…”
Section: Chemical Characteristicsmentioning
confidence: 99%
“…Changes in the climatic conditions of the orchard cultivation area affect not only the growth of the fruit tree but also the quality of the fruit, harvest time, and fruit storage. Therefore, several studies have been conducted to cope with climate change, leading to the successful development of varieties suitable for high-temperature, such as 'Sanggamdongsi' (Kim et al 2016). Furthermore, climate change also imposes serious threats regarding the increased incidence of diseases and pests.…”
Section: Introductionmentioning
confidence: 99%